Kreatifitas Pedagang Kaki Lima pada Masa Pandemi Covid-19 di Kecamatan Tamalate Kota Makassar - Sri Hardiyanti; Dimas Ario Sumilih (Rayhan Intermedia, 2022)
This research was conducted to find out: 1). What are the creativity of street vendors in marketing their goods during the Covid-19 period 2). What are the adaptation strategies implemented by street vendors in dealing with the COVID-19 pandemic. 3). What impact has the COVID-19 pandemic had on street vendors. This research uses a type of qualitative research, namely by describing the results of the research in narrative form. Data collection is done by conducting observations, interviews, and documentation. Validity test is done by triangulation technique. Data analysis techniques by means of data collection, data reduction stage, data display, verification and drawing conclusions. The research results show that 1). The creativity of street vendors in marketing their wares during the pandemic included making new products, such as updating their trading carts, to make them even more attractive to attract buyers. 2). The adaptation strategy adopted by street vendors in dealing with the Covid-19 pandemic, namely maintaining the quality of what is sold, selecting strategic locations and providing the best service to buyers. 3). The impact caused by the Covid-19 pandemic, including the impact of Covid-19 that is felt by street vendors is that their income has dropped dramatically which is influenced by the number of buyers and the prices of basic necessities have started to soar.